2020
DOI: 10.1101/2020.10.30.361238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual neuroscience methods for marmosets: efficient receptive field mapping and head-free eye tracking

Abstract: The marmoset has emerged as a promising primate model system, in particular for visual neuroscience. Many common experimental paradigms rely on head fixation and a sustained period of eye fixation during the presentation of salient visual stimuli. Both of these behavioral requirements can be challenging for marmosets. Here, we present two methodological developments to overcome these difficulties. First, we show that it is possible to use a standard eye tracking system without head fixation to assess visual be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 98 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Reverse correlation analysis was used to locate RF centers across the whole monitor. A detailed account of the RF mapping procedure can be found in Jendritza et al, 2021. As expected from the implantation target position, RFs in area V1 were located in the lower right visual field (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Reverse correlation analysis was used to locate RF centers across the whole monitor. A detailed account of the RF mapping procedure can be found in Jendritza et al, 2021. As expected from the implantation target position, RFs in area V1 were located in the lower right visual field (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…All details about the RF mapping procedure have been described previously in Jendritza et al, 2021. RF mapping was performed with stimuli consisting of black wedges and annuli of various orientations and sizes, presented on a gray background for a duration of eight frames (120 Hz monitor refresh rate).…”
Section: Receptive Field Mappingmentioning
confidence: 99%
“…A detailed account of the RF mapping procedure can be found in ref. 30 . As expected from the implantation target position, RFs in area V1 were located in the lower right visual field (Fig.…”
Section: Simultaneous Recording In Areas V1 and V6mentioning
confidence: 99%
“…All details about the RF mapping procedure have been described previously 30 . RF mapping was performed with stimuli consisting of black wedges and annuli of various orientations and sizes, presented on a gray background for a duration of eight frames (120 Hz monitor refresh rate).…”
Section: Receptive Field Mappingmentioning
confidence: 99%
“…Several neurological disease models have also been successfully generated using various methods in marmosets (Eslamboli et al, 2007; Tomioka et al, 2017; Jenner et al, 1984; Fox et al, 2010; Emborg, 2017). Moreover, they can learn to perform a variety of visual and cognitive tasks under head unrestrained conditions (Clarke et al 2011; Jendritza et al 2021; Spinelli et al 2004; Yamazaki et al 2011; Okano 2021) and under head restrained conditions (Mitchell et al 2014; Johnston et al, 2018; Chen et al, 2021; Sedaghat-Nejad et al 2019), and they showed similar to human behaviour when they successfully performed oculomotor tasks.…”
Section: Introductionmentioning
confidence: 99%